2017
DOI: 10.1039/c7ra04180b
|View full text |Cite
|
Sign up to set email alerts
|

A new guanylhydrazone derivative as a potential acetylcholinesterase inhibitor for Alzheimer's disease: synthesis, molecular docking, biological evaluation and kinetic studies by nuclear magnetic resonance

Abstract: Molecular docking, in silico studies and NMR show that the new guanylhydrazone is a promising compound for the treatment of Alzheimer's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 43 publications
2
8
0
Order By: Relevance
“…According Sugimoto et al [30], carbonyl groups conjugated to aromatic rings are important for inhibition of AChE. However, Ferreira Neto et al [25] showed that the presence of a guanyl-hydrazone allows interactions with the catalytic anionic site (CAS) of AChE, improving the activity, as also shown here.…”
Section: Resultssupporting
confidence: 57%
See 2 more Smart Citations
“…According Sugimoto et al [30], carbonyl groups conjugated to aromatic rings are important for inhibition of AChE. However, Ferreira Neto et al [25] showed that the presence of a guanyl-hydrazone allows interactions with the catalytic anionic site (CAS) of AChE, improving the activity, as also shown here.…”
Section: Resultssupporting
confidence: 57%
“…NMR is a good method for the biological evaluation of AChE inhibitors. Recent published works have indicated results consistent with Ellman’s method [25,32,33,34,35,36]. In our study we used the NMR method [29] to determine the concentrations of the substrate (ACh) and the product acetate (Ac), which are obtained from direct integration of the corresponding absorption peaks for methyl groups (2.24 ppm for ACh and 2.16 ppm for Ac) [32,35].…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…The choice of the TcAChE instead of an Electrophorus electricus model of AChE (which was employed for the Ellman assay) was based on the good resolution of the structure (2.5 Å), the similarity of the ligand in the structure with compound 4 and the unavailability of high resolution EeAChE structures. 47 It is worth noting the high degree of identity between TcAChE and EeAChE. 48 Water molecules and the original ligand were removed from the protein structure and polar hydrogens and charges were added.…”
Section: Molecular Modellingmentioning
confidence: 99%
“…A small turn of the nitro or hydroxyl groups would be needed for this to happen, but a weak interaction between them might be helping the interaction of 2d with this residue. The clearer interactions for 2d appear with Trp84, a residue that has been reported as an important one for ligand interactions (especially with quaternary groups from acetylcholine and other compounds) [58,62]. In this case, Trp84 is near the positively charged nitrogen of the nitro group, although its position appears to be almost over the B ring of the chalcone, allowing for π-π stacking at 3.7 Å.…”
Section: Molecular Docking Analysismentioning
confidence: 93%